PENYALAHGUNAAN NARKOTIKA, PSIKOTROPIKA, DAN ZAT ADIKTIF LAIN (NAPZA) SEBAGAI FAKTOR RISIKO NEUROPATI PERIFER PADA REMAJA JALANAN - , Suprapto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Narcotics, psychotropics, and addictive substances uses disorders increases widely in youth, especially homeless youth. The substances uses disorders impacts are serious, one of them is peripheral neuropathy. Many substances have direct toxic effects and neurotransmitter syntesis disturbances. The aim of this study was to know about substances uses disorders as a risk factor of peripheral neuropathy in homeless youth. The effects of number and duration of substances uses in peripheral neuropathy are still largely unknown. This is a case control study. Homeless youth between 18-24 years old with peripheral neuropathy as case group and without peripheral neuropathy as control group were recruited in this research. The Modified Total Neuropathy Score (mTNS) was used to asses peripheral neuropathy. Car, Relax, Alone, Forget, Friends, Trouble (CRAFFT) questionnaire was used to asses substances uses disorders. A total 88 subjects were recruited for study, which each case and control group have 44 subjects. Thirthy five subjects in case group and 12 subjects in control group are suffer substances uses disorders. Substances uses disorders increase the risk of peripheral neuropathy in homeless youth (OR=12,50